Ageing, Health and Pensions in Europe - Bovenberg, Lans. author. aut Link
XIV, 400 p.
Keywords: Providing an overview of the future research challenges for economists and social scientists concerning population ageing, pensions, health and social care in Europe, this book examines how scientific research can provide cutting-edge evidence on income security and well-being of the elderly, and labour markets and older workers.